Features of Higher Education in Europe: On the Example of France - Abdukhalikovna, Mamadkulova Kamila; Khinzhihon, Rustamova (Research Parks Publishers, 2023)
The article discusses the types of education in France: primary, secondary and higher. France ranks first among non-English speaking countries in terms of the number of international students studying in it. Every third doctoral degree here is awarded to a foreigner.